Bad environmentalism : irony and irreverence in the ecological age - Seymour, Nicole (University of Minnesota Press, 2018)
"Bad Environmentalism examines how contemporary artists identify and respond to the ironies and absurdities surrounding environmental activism with their work in film, reality TV, poetry, fiction, performance art, and standup comedy. Focusing on texts such as the TV show Wildboyz and film series Green Porno, the book shows how such "bad environmentalists" use absurdity, camp, playfulness, and repulsiveness to counter climate skepticism and forces of environmental degradation as well as to question mainstream environmentalism's earnest prescriptiveness. Using affect theory and queer theory as her primary theoretical frameworks, Seymour considers the potentials and pitfalls of bad environmentalism and expands our understandings of environmental art and activism"--